42. THE RESULTS OF MANAGEMENT OF TUBERCULOSIS TREATMENT COMPLIANCE AND SOME AFFECTING FACTORS AMONG TUBERCULOSIS PATIENTS AT THE HEALTH CENTER OF BINH DONG AREA IN HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2026)
Background: Tuberculosis is one of the top 10 leading causes of death worldwide, surpassing HIV. According to estimates by the World Health Organization (WHO), in 2015 there were approximately 10.4 million new cases of tuberculosis and 1.4 million deaths due to the disease. Vietnam is one of the 30 countries with the highest burden of tuberculosis in the world, with around 174,000 new cases and 11,000 deaths annually. Binh Dong Area is one place with a high incidence of both drug-susceptible and drug-resistant tuberculosis in Ho Chi Minh City. In addition, changing the tuberculosis drug regimen using the health insurance fund has brought about changes in the management of treatment adherence among tuberculosis patients (TB). Therefore, there is a need for a study to evaluate the management of treatment adherence among tuberculosis patients in this area in order to identify the challenges in management and improve the effectiveness of tuberculosis management of patients inthis area.Objectives: Results of the management and treatment of tuberculosis patients at the Health Center of Binh Dong Area in Ho Chi Minh City and some influencing factors.Methods: A cross-sectional study combining quantitative and qualitative research was carried out on 213 TB patients and health worker.Results: The proportion of TB patients with correct general knowledge about TB reached 14.1%. Regarding adherence to treatment principles, patients who adhered to all 5 treatment principles achieved the highest rate of 40.4%. Finding the relationship between some background characteristics of the study subjects such as age group, occupation, education level and patient's adherence to TB treatment. Some influencing factors such as Policy, Human Resources, Funding, Socio-economic characteristics.Conclusion: The management of TB treatment adherence of TB patients at the Health Center of Binh Dong Area has been well done. However, it is necessary to have policies to attract funding and attract human resources to improve the effectiveness of TB treatment adherence management in this area.
Keywords: Management, adherence to treatment, tuberculosis.